Pengaruh Religiusitas, Brand Loyalty, Label Halal, Label BPOM dan Harga Terhadap Keputusan Pembelian Produk Kosmetik Wardah Halal - Marita Putri; Miti Yarmunida; Miko Polindi (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to measure the influence of religiosity, brand loyalty, halal label, BPOM label, and price on the purchase decision of Wardah halal cosmetic products. This research is a research study. The data type used is primary data sourced from a questionnaire. The study population consisted of residents of Pagar Dewa Village, with a sample of 97 respondents. The data analysis technique used was multiple linear regression analysis with SPSS 25 software. The results of the study indicate that 1) Religiosity has a significant influence on the purchase decision of Wardah cosmetic products. (2) Brand Loyalty has a significant influence on the purchase decision of Wardah cosmetic products. (3) The Halal Label has a significant influence on the purchase decision of Wardah cosmetic products. (4) The BPOM label significantly influences purchasing decisions for Wardah cosmetic products. (5) Price significantly influences purchasing decisions for Wardah cosmetic products. Religiosity, brand loyalty, the halal label, the BPOM label, and price simultaneously have a positive and significant influence on purchasing decisions for Wardah halal cosmetic products.